Improving capacity and consent to treatment recording in psychiatric inpatient wards: A multi-centre quality improvement project. Issue 1 (28th December 2016) - Li, Ching; Stellman, Judith; Patel, Nitisha; Dalton, Florence
Abstract : Assessment of mental capacity provides an ethical and legal framework for care which values patients' autonomy whilst recognising the instances where it is appropriate to act in patients' best interests. Existing medical literature indicates that mental capacity is poorly documented in psychiatric inpatient settings. The aim of the project was to examine the frequency of capacity and consent to treatment documentation with a view to creating changes in practice by raising awareness about the importance of assessing and documenting mental capacity. A multi-centre quality improvement project was conducted in September 2014 across all general adult psychiatric inpatient wards in the North Central London Training Scheme. The frequency of documentation of capacity and consent to treatment for all adult psychiatric inpatient wards across North Central London was measured. Electronic patient notes were audited retrospectively to ascertain whether capacity and consent to treatment on admission, and within the preceding seven days of data collection, was recorded. Data was collected across three successive time points during a 12 month period following the implementation of changes. A total of 232 patients were included in the baseline measurements. The results highlighted a deficiency in the recording of capacity and consent to treatment for adult psychiatric inpatients. The results showed that, of the patients audited, 49.8% had their capacity and consent to treatment assessed on admission, 61.9% had a capacity assessment in the previous 7 days and 60.5% had consent recorded in the previous 7 days. These findings were presented at local hospital teaching sessions at each of the audited sites. These sessions also gave teaching on mental capacity. Audit cycle 1 was conducted 6 months later, this included 213 patients and showed a 30% improvement in the frequency of documentation across all measures. The results showed that 77% of patients audited had their capacity and consent assessed on admission to the ward, 87.3% had a capacity assessment in the previous 7 days and 85.5% had consent recorded in the previous 7 days. After feedback from the teaching sessions, a clerking proforma was produced that had a prompt to assess to capacity. Audit cycle 2 was conducted 12 months after the initial baseline measurements, had a sample size of 229 patients and a sustained improvement in documentation of 26% from baseline was demonstrated across all measures. This project demonstrated that capacity and consent to treatment was not routinely recorded but that the frequency of recording improved through the use of teaching sessions on mental capacity and the introduction of admission clerking proformas with capacity prompts.